The LIVE Network: A Music-Based Messaging Program to Promote ART Adherence Self-Management - Holstad, Marcia McDonnell (2013)
We developed and pilot-tested the efficacy, acceptability, and feasibility of a music program, The LIVE Network (LN), compared to standard care on outcomes of ART adherence, clinical indicators, and self-efficacy. The study was powered to detect differences at p < 0.1. We enrolled and followed 77 participants for 12 weeks (T3). Mean monthly pill counts (PC) declined over time in both groups. Although not significant, the LN had higher PC and a larger proportion had plasma anti-retroviral trough levels within therapeutic range. The LN group did have significantly (p < 0.1) increased levels of adherence self-efficacy and decrease in viral loads.